Effect of chemical composition on particle morphology of topologically close-packed precipitates in a Ni-based single crystal superalloy. (December 2018) - Long, Haibo; Liu, Yinong; Mao, Shengcheng; Wei, Hua; Zhang, Jianxin; Ma, Shiyu; Deng, Qingsong; Chen, Yanhui; Zhang, Ze; Han, Xiaodong
Abstract: Topologically close-packed (TCP) phases in Ni-based single crystal superalloys are known to exhibit different morphologies and orientation relationships within the matrix. This study investigated the influence of chemical composition on lattice parameters, which in turn determine the interface lattice misfit between TCP phase and matrix and thus shape and orientation of the TCP phase. In this study, TCP phase particles of different morphologies were formed by ageing at different temperatures. The level of TCP-phase element enrichment was found to increase with increasing growth time and ageing temperature, and thus leads to a same evolution behavior of the atomic volume. Graphical abstract: Unlabelled Image